Comparison of resistance and stretching exercises in women with primary dysmenorrhea: A randomized controlled trial - Öz, Ayşe; Yana, Metehan (SAGE Publications, 2025)
Objective This study compared the effects of resistance and stretching exercises on menstrual symptoms, quality of life, and functional and emotional status in young women with primary dysmenorrhea. Methods In this randomized controlled trial, 54 women (18–25 years) with primary dysmenorrhea were assigned to stretching (n = 17), resistance (n = 19), or control (n = 18) groups. Outcomes were assessed using the Visual Analog Scale (VAS), Menstrual Symptoms Questionnaire (MSQ), Pittsburgh Sleep Quality Index (PSQI), Health-Related Quality of Life (SF-36), and Functional and Emotional Measure of Dysmenorrhea (FEMD). Assessments were conducted before the intervention and over two menstrual cycles. Exercise groups trained three times weekly for eight weeks. Results VAS, MSQ, PSQI, and FEMD scores significantly decreased in both exercise groups compared to the control group (p < 0.05). SF-36 scores were significantly higher in both exercise groups (p < 0.05). Post-treatment, medication use decreased significantly. Subdimension analyses revealed improvements in SF-36 and reductions in MSQ and FEMD subdimensions. No significant differences were found between the resistance and stretching groups in the primary outcomes (p > 0.05). Conclusion Both resistance and stretching exercises reduce menstrual symptoms and improve quality of life. No significant difference was found; women may choose stretching or strengthening exercises based on personal preference.